A qualitative study of the psychosocial implications of lipodystrophy syndrome on HIV positive individuals. Issue 2 (1st April 2003) - Power, R; Tate, H L; McGill, S M; Taylor, C
Abstract : Objectives: To investigate the psychosocial impact of lipodystrophy on the lifestyles of HIV positive patients on highly active antiretroviral therapy (HAART). Methods: In-depth interviews were conducted with 14 HIV positive patients on HAART at an outpatient sexually transmitted infections (STI) and HIV clinic in central London. Qualitative data from interview transcripts were analysed using grounded theory to elicit key categories and subcategories. Results: Three main themes relating to lipodystrophy emerged: effect on the individual; impact on the social world of the individual; responses of the individual. Lipodystrophy had physical and psychological effects, ranging from bodily discomfort to low self esteem and depression. Owing to its physical manifestations it was viewed as a visible marker of HIV disease. At the level of social functioning, lipodystrophy led to problems with personal and family relationships, although having a partner was protective. Individuals reported narrowing their social world, in some cases to degrees of social isolation. Individual responses included changes in diet, increased exercise regimes, steroid use and plastic surgery (mainly collagen injections to the face). For those who had experienced serious illness related to HIV, there was a more sanguine acceptance of lipodystrophy as an unfortunate consequence of longevity and drug therapy Conclusions: Health professionals need to address the psychosocial implications of lipodystrophy, including the ways in which it may affect different groups and their adherence to therapy. Formative evaluations are needed to assess the potential for targeted interventions.